Strategi Pengembangan Desa Wisata Berbasis Wisata Agro di Desa Nglinggo Kabupaten Kulon Progo - Edouard Aryadi Supriyadi; Emanuela Agra Sarika Kurnia Dewi (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
The Special Region of Yogyakarta is widely known by the people of Indonesia as an area that still has many unspoiled areas for the construction of cutting-edge complexes. This type of tourism has become the most time-keeping vacation style and is popular in the eyes of the public today after several years of experiencing limited activities due to the COVID-19 pandemic. This has resulted in the emergence of a type of special interest tourism, namely alternative tourism called Tourism Village. Nglinggo Hamlet Tourism Village develops slowly through word of mouth and is able to move the local Hamlet community independently to play an active role in utilizing all sectors that can be used as tourist attractions. The method used in this study is descriptive qualitative. Data collection techniques use observation, literature studies and interviews with several speakers. The use of SWOT analysis in this study is to systematically identify various factors aimed at formulating a strategy for developing the Nglinggo tea garden agro-tourism village. The results of this study show that there are strategies such as, SO, WO, ST, WT, to develop a tourist village, in Yogyakarta, Nglinggo in its opportunity to develop a tourist village to reach the peak of its success.